Advance research progresses in aluminium matrix composites: manufacturing & applications - Garg, Pulkit; Jamwal, Anbesh; Kumar, Devendra; Sadasivuni, Kishor Kumar; Hussain, Chaudhery Mustansar; Gupta, Pallav (Elsevier Editora Ltda, 2019)
At present aluminium matrix composites are widely used in engineering applications. Aluminium matrix composites are providing such superior properties which cannot be achieved by any existing monolithic material. Properties of aluminium matrix composite are highly influenced by nature of reinforcement which can be either in continuous or discontinuous fibre form. It also depends on the selection of processing techniques for the fabrication of aluminium matrix composites which depends on many factors including type of matrix and reinforcement, the degree of microstructural integrity desired and their structural, mechanical, electrochemical and thermal properties. Present paper reports an overview on synthesis routes, mechanical behavior and applications of aluminium matrix composites. Special focus is given to primary processing techniques for manufacturing of aluminium matrix composites. In the end, commercialization challenges, industrial aspects and future research directions are also briefed.
Keywords: Aluminium matrix composites (AMCs); Commercialization; Industrial applications; Mechanical behavior; Powder metallurgy; Stir casting